2015
DOI: 10.1007/s00586-015-4188-3
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic adjacent segment degeneration at the L3–4 level after fusion surgery at the L4–5 level: evaluation of the risk factors and 10-year incidence

Abstract: We determined six significant factors affecting CASD development. Among these risk factors, facet degeneration, isthmic-type spondylolisthesis, and the type of fusion show higher hazard ratios and seem to be clinically more relevant than the other three factors (age, overall lordosis, and segmental lordosis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Various risk factors for ASD after one-segment fusion have been reported, including age and sex, preoperative adjacent disc degeneration, sagittal malalignment, number of segments fused, laminar inclination, facet tropism, and excessive distraction of the disc space 6,[12][13][14][15][16][17][18][19] . However, in the present study, there was no significant association of age, sex, or preoperative disc degeneration with RASD, and the only risk factor was a preoperative absolute value of UIV tilt >10°(i.e., preoperative UIV tilt > 10°or UIV tilt < −10°).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various risk factors for ASD after one-segment fusion have been reported, including age and sex, preoperative adjacent disc degeneration, sagittal malalignment, number of segments fused, laminar inclination, facet tropism, and excessive distraction of the disc space 6,[12][13][14][15][16][17][18][19] . However, in the present study, there was no significant association of age, sex, or preoperative disc degeneration with RASD, and the only risk factor was a preoperative absolute value of UIV tilt >10°(i.e., preoperative UIV tilt > 10°or UIV tilt < −10°).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of risk factors for ASD after lumbar spine fu-sion surgery have been reported, including the length of the fusion, sagittal malalignment, age and sex, preoperative ASD, laminar inclination, facet tropism, and excessive disc distraction 6,[12][13][14][15][16][17][18][19] . It is known that the greater the number of fused segments the greater the risk of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…The increased rigidity conferred by the addition of an interbody device may contribute to elevated rates of adjacent segment degeneration (ASD) and compression fracture [23][24][25][26]. However, conflicting data indicate that IBF may instead protect against ASD by generating more segmental lordosis [27].…”
Section: Indications For Interbody Fusionmentioning
confidence: 99%
“…Though rigid fusion has been proved to be an effective way to restore the disc space height, reconstruct the stability and alignment of spine, a variety of complications had emerged such as adjacent segment disease with the change of spinal mechanical activities [12]. The rigid fusion decreased the flexibility and mobility of the entire lumbar spine, leading to the center of rotation of vertebral body shifts over the disc, consequently, the stress on the facets and/or disc of the adjacent mobile segment significantly increased [4]. The increased stress will lead to a significant effect on intersegmental mobility and the increase in intradiscal pressure, overall, it accelerates degenerative changes at adjacent unfused segment, especially at the cranial level [13].…”
Section: Discussionmentioning
confidence: 99%
“…Due to spinal fusion surgery has significantly facilitated patient comfort and mobility, fusion is regarded as a gold standard treatment for degenerative lumbar spine disease. However, we cannot ignore the fact that many researchers have demonstrated that fusion can accelerate the degeneration of adjacent lumbar segment, due to it can lead to excessive stress at unfused adjacent levels [4,5]. Therefore, society of spine surgery holds the promise to develop an effective method to prevent or slow down the progress of adjacent segmental degeneration (ASD), after surgical treatment of lumbar degenerative disorders [6].…”
Section: Introductionmentioning
confidence: 99%